Detection and decoding for two-dimensional interference channels - Yao, Jun (2013)
In this thesis, we study the problem of communication over two-dimensional (2-D) interference channels which represent an important class of data storage and communication systems. The maximum-likelihood page detection (MLPD) for 2-D interference channels is firstly studied and the lower and upper performance bounds are derived.